Hearing loss before and after cisplatin-based chemotherapy in testicular cancer survivors: a longitudinal study. (3rd August 2018) - Haugnes, Hege S.; Stenklev, Niels Christian; Brydøy, Marianne; Dahl, Olav; Wilsgaard, Tom; Laukli, Einar; Fosså, Sophie D.
Abstract: Background: Hearing loss is a well-known long-term effect after cisplatin-based chemotherapy (CBCT) in testicular cancer survivors (TCS), but longitudinal data are sparse. We evaluate hearing loss and the impact of age in TCS treated with CBCT in this longitudinal study. Material and methods: Forty-six TCS treated with CBCT 1980–1994 with audiograms (0.25–8 kHz) pre-chemotherapy (PRE) and at a follow-up survey (SURV) after median 10 years were included (cases). Audiograms at SURV from 46 age-matched TCS without CBCT were included as controls. Linear regression was performed to evaluate predictors for change in the hearing threshold level (HTL) from PRE to SURV. Two definitions of a audiogram-defined hearing loss was applied if: (1) mean HTL for both ears exceeded 20 dB at any frequency 0.25–8 kHz (American Speech-Language-Hearing Association (ASHA) definition) and (2) average HTL for the frequencies 0.5, 1, 2 and 4 kHz exceeded 20 dB (WHO-M4 definition). Self-reported hearing impairment (SURV) was assessed by a questionnaire. Results: Age and cisplatin dose was significantly associated with a greater change in HTL for the frequencies 2–8 kHz. For the 8 kHz frequency, each 100 mg increase in cumulative cisplatin dose was associated with a deterioration of 3.6 dB (95% CI 1.8–5.3, p < .001). The prevalence of hearing loss (ASHA) among cases was 33% PRE, 70% at SURV and 65% among controls at SURV (cases vs. controls, p = .66). According to M4, the prevalence of hearing loss among cases was 6.5% PRE, 13% at SURV and 2.2% among controls at SURV (cases vs. controls, p = .049). Twenty-nine percent of cases, and 33% of controls ( p = .70) reported hearing impairment at SURV. Conclusion: Cisplatin is associated with a hearing loss particularly at higher frequencies. Age appear to be an important factor for hearing loss regardless of treatment. The ASHA definition overestimates the hearing problem.